Impact of R&D Investment on Economic Growth and Industry Competitiveness in Indonesia - Judijanto, Loso (Westscience Press, 2024)
This study examines the impact of research and development (R&D) investment on economic growth and industrial competitiveness in Indonesia, focusing on 55 industrial sectors. Using a quantitative approach, data were collected through a structured Likert scale survey and analyzed with SPSS version 26. The results demonstrate a significant positive relationship between R&D investment and both economic growth and industrial competitiveness. Regression analysis reveals that R&D investment accounts for 58% of the variance in economic growth and 62% of the variance in industrial competitiveness. These findings highlight the pivotal role of R&D in fostering innovation, enhancing productivity, and achieving global competitiveness. Policymakers and industry stakeholders are encouraged to prioritize R&D funding to drive sustainable economic development in Indonesia.